2023
DOI: 10.18502/jthc.v17i4.11609
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diabetes Mellitus on Clinical Outcomes after Percutaneous Coronary Intervention with Different Stent Sizes

Abstract: Background: This study aimed to investigate the possible relationship between different stent sizes and clinical outcomes after percutaneous coronary intervention (PCI) in patients with diabetes treated with drug-eluting stents (DESs) and dual antiplatelet therapy (DAPT). Methods: Patients with stable coronary artery disease undergoing elective PCI with the DES were entered into a retrospective cohort between 2003 and 2019. Major adverse cardiac events (MACE), defined as the combined endpoint of revascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Nonetheless, overly aggressive postdilatation could potentially lead to higher rates of vessel injury, coronary dissection, and neointima response, which, in consequence, could cause ischemic events in the future. In this context, one study showed that the stent’s diameter and length did not impact the outcomes of DM patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, overly aggressive postdilatation could potentially lead to higher rates of vessel injury, coronary dissection, and neointima response, which, in consequence, could cause ischemic events in the future. In this context, one study showed that the stent’s diameter and length did not impact the outcomes of DM patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 The latest estimates in 2017 indicated that 451 million people the world over had diabetes, with the figure projected to have risen to 693 million by 2045. 3 Diabetes imposes a significant burden on society in terms of expenses, premature death, and intangible costs in reduced quality of life. 4 …”
Section: Introductionmentioning
confidence: 99%